New Hermitian self-dual MDS or near-MDS codes over finite fields - Djoko Suprijanto (Institute for Research and Community Services (LPPM) ITB, 2014)
A linear code over a finite field is called Hermitian self-dual if the code is self-dual under the Hermitian inner-product. The Hermitian self-dual code is called MDS or near-MDS if the code attains or almost attains the Singleton bound. In this paper we construct new Hermitian self-dual MDS or near-MDS codes over and of length up to 14.